Medicinal plants used in the Barros Area, Badajoz Province, Spain. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)